Advanced ZnSnS3@rGO Anode Material for Superior Sodium‐Ion and Lithium‐Ion Storage with Ultralong Cycle Life. Issue 4 (27th December 2018) - Jia, Hao; Dirican, Mahmut; Sun, Na; Chen, Chen; Yan, Chaoyi; Zhu, Pei; Dong, Xia; Du, Zhuang; Cheng, Hui; Guo, Jiansheng; Zhang, Xiangwu
Abstract: A novel and facile approach has been utilized to synthesize zinc tin sulfide@reduced graphene oxide (ZnSnS3 @rGO) through aqueous reaction of Na2 SnO3 and Zn(CH3 COO)2, combined with a subsequent solvothermal reaction and an annealing process. The as‐prepared ZnSnS3 @rGO nanocomposite exhibited an excellent sodium‐ and lithium‐ion‐storage performance with large specific capacity, high rate capability, and ultralong cycle life. When used in Na‐ion cells, the ZnSnS3 @rGO nanocomposite delivered a capacity of 472.2 mAh g −1 at 100 mA g −1 and retained a specific capacity of 401.2 mAh g −1 after 200 cycles. In Li‐ion cells, the ZnSnS3 @rGO nanocomposite delivered a capacity of 959.2 mAh g −1 at a current density of 100 mA g −1 and maintained a specific capacity of 551.3 mAh g −1 at a high current density of 1 A g −1 upon 500 cycles. The electrochemical performance results reveal that the integration of uniformly dispersed metal elements and an interconnected carbon matrix could help release the stress of volumetric excursion and provide fast electron/ion transport, leading to a remarkable electrochemical performance. Abstract : The anode material ZnSnS3 @rGO is rationally synthesized by uniformly anchoring ZnSnS3 nanosheets on highly conductive reduced graphene oxide (rGO) sheets. Integration of uniformly dispersed metal elements and the interconnected carbon matrix provides fast electron/ion transport and helps to release the stress of volumetric excursion, leading to a high capacity and good cycling stability. The as‐prepared ZnSnS3 @rGO material exhibits an outstanding electrochemical performance for both sodium‐ion and lithium‐ion batteries.